Eksodus sebagai Paradigma Kebebasan Spiritual: Analisis Kritis Teologi Pembebasan dalam Perjanjian Lama - Andreas Christanto; Netti Uli Manullang (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
The transition from Mount Sinai to Mount Zion in biblical tradition highlights the progressive nature of God's plan of salvation, combining justice and grace. Mount Sinai represents establishing a covenantal community by giving the law, while Mount Zion portrays the eschatological reality of peaceful fellowship with God through divine grace. This journey teaches that true freedom involves adherence to justice and moral responsibility values, culminating in divine grace. This transition is relevant as a paradigm for building inclusive, just, and harmonious communities in the modern context. The church is called to integrate the principles of Sinai's justice and Zion's grace in its ministry, creating spaces for inter-community dialogue and promoting social justice. By merging the aspects of law and grace, the church can become an agent of social transformation, reflecting God's character in a world rife with injustice.